MOSSBAUER, TEM/SAED AND XRD INVESTIGATION ON WASTE DUMPS OF THE VALEA LUI STAN GOLD MINES (PANGEEA, 2025)
ABSTRACT: The complementary investigation techniques, Mossbauer spectroscopy, transmission electron microscopy with selected area electron diffraction (TEM/SAED), X-ray diffraction (XRD) have been used to investigate the fate of the Valea lui Stan, Romania, gold-ore nanoscale-minerals during the long time of residence in the waste dumps. The preliminary investigations showed such waste dumps to contain significant amount of metals which cannot be identified by conventional methods. An intense research activity started up in order to evaluate the possibilities to recycle Valea lui Stan waste dumps and to recover metals by chemical or phytoextraction procedures. The waste dumps naturally show different mineral constituents with clay minerals as major phases, observed by XRD-technique. Although the waste dumps materials have whitish-yellowish colours, MOSSBAUER technique evidences the presence of the finely dispersed iron bearing minerals. The authors are focusing to inspect and analyze Fe-compounds in the samples collected from Valea lui Stan's waste dumps in order to identify the magnetic phases by Mossbauer technique.
Keywords: Mossbauer; TEM/SAED; XRD; Waste dumps; Iron oxides